2008
DOI: 10.3399/bjgp08x263811
|View full text |Cite
|
Sign up to set email alerts
|

Managing earwax in primary care: efficacy of self-treatment using a bulb syringe

Abstract: Irrigating ears to remove wax is a time-consuming procedure in UK primary care. In many other countries bulb syringes are used for self-clearance of earwax but evidence of their effectiveness is lacking. AimTo compare the effectiveness of self-treatment bulb syringes with routine care. Design of studyOpen, randomised, controlled trial. SettingSeven practices in Hampshire, UK. MethodParticipants were 237 patients attending their GP or practice nurse with symptomatic occluding earwax. A further 128 patients did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 3 publications
0
26
1
Order By: Relevance
“…Table 1 shows that the term 'usual care' was used in 33 of the 73 articles. Other expressions were also used, such as 'routine care', 15,29,35,63 'usual practice', 41 'normal care', 34 'standard care', 49,78 'care as usual', 55 'usual policy', 60 'usual service', 76 and 'usual management'. 84 Other authors did not use a specific expression.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows that the term 'usual care' was used in 33 of the 73 articles. Other expressions were also used, such as 'routine care', 15,29,35,63 'usual practice', 41 'normal care', 34 'standard care', 49,78 'care as usual', 55 'usual policy', 60 'usual service', 76 and 'usual management'. 84 Other authors did not use a specific expression.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Coppin and colleagues, 63 at baseline 63% of participants in the self-irrigation group had a completely occluded right ear and 67% a completely occluded left ear. In the nurse irrigation group these proportions were similar (62% with completely occluded right ear and 69% with a completely occluded left ear).…”
Section: Measures Of Occlusionmentioning
confidence: 99%
“…Two RCTs 63,64 investigated the use of self-irrigation after participants had been assessed for earwax in primary care. One 63 compared self-irrigation to nurse irrigation in adult participants who had been given sodium bicarbonate to use for at least 2 days.…”
Section: Studies Of Self-carementioning
confidence: 99%
“…Study sample sizes were typically small, varying from 36 participants 45 to 237 participants, 63 and only a few studies reported undertaking a sample size calculation (7 out of 24 studies 45,47,49,52,53,56,63 ). In some studies the overall population sample size was not reported, rather the numbers of ears were presented.…”
Section: Quantity and Quality Of Research Availablementioning
confidence: 99%
“…These trials fell into three categories: studies undertaken in primary care (14 studies [41][42][43][44][45][46][47][48][49][50][51][52][53][54] ), studies undertaken in secondary care (eight studies 4,[54][55][56][57][58][59][60] ), and studies of self-care or those undertaken in other care settings (four studies [61][62][63][64] ). Where the setting was in emergency care this has been grouped under primary care in the present review because it was assumed that this was the first point of contact with a health professional.…”
Section: Quantity and Quality Of Research Availablementioning
confidence: 99%